Cross-sectional study of correlates and prevalence of functional and high-risk multimorbidity in an academic HIV practice in New York City - Elizabeth Mauer; Eugenia Siegler; Jerad Moxley; Marshall Glesby (BMJ Open)
Objectives People with HIV have high levels of multimorbidity, but studies often focus on high-risk comorbidities such as hypertension or coronary artery disease. We examined both high-risk and functional comorbidities in an ethnically diverse clinic population to compare the prevalence of comorbidities and different patterns of multimorbidity.Design Retrospective cross-sectional study.Setting University-based primary care HIV clinic with two locations in New York City.Participants Patients who had been seen by a physician at least once between 1 June 2016 and 31 May 2017.Primary and secondary outcome measures Data regarding demographics, diagnoses and lab values were downloaded in a one-time data import from the electronic medical record. Comorbidities were classified as high-risk (with major impact on mortality) or functional (with major impact on function), and multimorbidity was determined for both classes in the total sample of 2751. Factors associated with high-risk and functional multimorbidity were determined first through bivariate analysis and then through multivariable median regression in 2013 patients with complete data.Results Median age was 52 years (IQR 43–59). Cisgendered women comprised 24.6% of the sample, and 31.7% were African-American. Both functional and high-risk comorbidities were common and risk increased with age. Among those 75 and older, median number of both functional and high-risk comorbidities was 3 (IQR 2–4). High-risk comorbidities were associated with age (p<0.001), more years with an HIV diagnosis (p<0.001) and being an African-American (p<0.001). Associated with a higher number of functional comorbidities were age (p<0.001), being a cisgender female (p<0.001), being Hispanic (p=0.01) and more years with an HIV diagnosis (p<0.001).Conclusions Comorbidities with functional impact increase with age in parallel to those with a more direct impact on mortality and should be assessed and monitored, especially as the population with HIV ages.